Looking Beyond Physical Disability: Cognitive Impairment in Persons With Multiple Sclerosis. Issue 5 (12th September 2022) - Lott, Shelley; Koszalinski, Rebecca; Hurt, Maria; Harris, Robin
Abstract: Purpose: Cognitive impairment (CI) is an underestimated part of disability in persons with multiple sclerosis (PwMS). The purpose of this evidence-based project was to influence clinicians treating PwMS by education of the current guidelines on cognition and multiple sclerosis and to screen CI with a valid neuropsychological tool. Methods: Staff were educated on the 2018 National Multiple Sclerosis Society guidelines about CI in PwMS. The Processing Speed Test (PST) measured CI. Results: Of 50 eligible patients in a 3-month period, 21 (42%) PwMS were cognitively screened. Of the 21 enrolled patients, nine (42.9%) patients were cognitively impaired. Employed patients' PST scores tended to be higher than unemployed patients. As age increased, PST raw scores decreased. Conclusions: In this project, less than half of eligible patients received cognitive screening after an extensive education program. Thus, education alone was not sufficient to change behavior. Other strategies to influence change may be more effective.